Working Memory and Cross-Frequency Coupling of Neuronal Oscillations - Abubaker, Mohammed; Al Qasem, Wiam; Kvašňák, Eugen (Frontiers in Psychology, 2021)
Working memory (WM) is the active retention and processing of information over a period of a few seconds and is considered an essential component of cognitive function. Reduced WM capacity is a common feature in many diseases such as schizophrenia, attention deficit hyperactivity disorder (ADHD), mild cognitive impairment (MCI), and Alzheimer`s disease (AD). The theta-gamma neural code is an essential component of memory representations in multi-item WM. Large body of studies have examined the association between cross-frequency coupling (CFC) across cerebral cortices and WM performance; electrophysiological data together with behavioural results showed associations between CFC and WM performance. Oscillatory entrainment (sensory, non-invasive electrical / magnetic, and invasive electrical) remains the key method to investigate the causal relationship between CFC and WM. Frequency-tuned non-invasive brain stimulation is a promising way to improve WM performance in healthy and non-healthy patients with cognitive impairment. Basically, WM performance is sensitive to the phase and rhythm of externally applied stimulations. CFC-transcranial-alternating current stimulation (CFC-tACS) is a recent approach in neuroscience that could alter cognitive outcomes. Studies that investigated 1) the association between CFC and WM and 2) brain stimulation protocols that enhanced WM through modulating CFC by the mean of non-invasive brain stimulation techniques have been included in this review. In principle, this review can guide the researchers to identify the most prominent form of CFC associated with WM processing (e.g., theta/gamma phase-amplitude coupling), and to define the previously published studies that manipulate endogenous CFC externally to improve WM. This in turn, will pave the path for future studies aimed at investigating CFC-tACS effect on WM. CFC-tACS protocols need to be thoroughly studied before they can be considered as therapeutic tools in patients with WM deficits.